Does orientation matter? Controlling laccase orientation on planar gold electrodes - Perry, Collin, author; Ackerson, Christopher, advisor; Snow, Christopher, committee member; Dandy, David, committee member; Neale, Nathan, committee member (Colorado State University. Libraries, 2024)
Enzyme electronics are becoming more common in modern life. Even though these technologies have been integrated into everyday life, the fundamental understanding of how an enzymes' orientation at the electrode surfaces affects the enzymes catalysis is still unknown. To understand this more we designed a library of laccase mutants, all with a single solvent exposed cysteine. These cysteine residues are used to bind to a gold electrode modified with a monolayer of sulfhydryl molecules capped with a maleimide binding group. Each mutants' single cysteine will bind to the maleimide group orienting each mutant differently at the electrode surface. The wild type enzyme (WT) and all the mutants, D113C, N264C, H470C all show activity toward a common substrate 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). Although each mutant does show catalytic activity in solution, we were unable to obtain an electrochemical response from the laccase library using the maleimide capped electrodes for either ABTS or oxygen. Modification of the electrodes via the deposition gold clusters makes the electrode surface more topographically complex. The cluster modified electrodes bound with WT laccase displayed an electrochemical response for the reduction of oxygen to water. The increased topography from using gold clusters allows for electron transfer with laccase enzymes, while the planar electrodes modified with the laccase enzymes in which we achieved an electrochemical response.
Keywords: gold; electrochemistry; laccase